Mass transport corrected Tafel analysis for electrochemically reversible systems of complex stoichiometry - Klymenko, O; Compton, R (2004)
An expression which allowed Tafel analysis of electrochemically reversible systems at hydrodynamic electrodes such as the rotating disk was investigated. It was found that under hydrodynamic conditions the mass transport of species occured within a diffusion layer of thickness δD adjacent to the surface of the electrode. Newton's method was used for solution of generally non-linear algebric equations arising from discretization. The results show that Tafel analysis of the simulated waveshapes reveals the deviation from the prediced values.